Optimization of Recruitment Process for AI Smart Home Startups in China - Zhou, Die (Curtin University, 2020)
To establish a better HR practice by incorporating the well-being parameters as well, this study focuses on developing mathematical models for activities in the recruitment process of the Chinese AI Smart Home startups. The superiority of the proposed optimization models, relative to the existing situations and methods, is further numerically demonstrated.